Atmospheric Gravity Waves Observed in the Nightglow Following the 21 August 2017 Total Solar Eclipse. Issue 17 (5th September 2020) - Paulino, I.; Figueiredo, C. A. O. B.; Rodrigues, F. S.; Buriti, R. A.; Wrasse, C. M.; Paulino, A. R.; Barros, D.; Takahashi, H.; Batista, I. S.; Medeiros, A. F.; Batista, P. P.; Abdu, M. A.; et al.
Abstract: Nighttime airglow images observed at the low‐latitude site of São João do Cariri (7.4°S, 36.5°W) showed the presence of a medium‐scale atmospheric gravity wave (AGW) associated with the 21 August 2017 total solar eclipse. The AGW had a horizontal wavelength of ∼1, 618 km, observed period of ∼152 min, and propagation direction of ∼200° clockwise from the north. The spectral characteristics of this wave are in good agreement with theoretical predictions for waves generated by eclipses. Additionally, the wave was reverse ray‐traced, and the results show its path crossing the Moon's shadow of the total solar eclipse in the tropical North Atlantic ocean at stratospheric altitudes. Investigation about potential driving sources for this wave indicates the total solar eclipse as the most likely candidate. The optical measurements were part of an observational campaign carried out to detect the impact of the August 21 eclipse in the atmosphere at low latitudes. Plain Language Summary: The Moon's shadow during a total solar eclipse introduces horizontal temperature gradients in the atmosphere and screens the ozone layer from solar heating. The shadow also travels supersonically, producing instabilities that can generate the so‐called atmospheric gravity wave (AGW). AGWs associated with eclipses are expected to have periodic oscillations with periods ranging from just a few minutes to hours. Additionally, these AGWs can have horizontal wavelengths as large as thousands of kilometers. It is also possible to estimate the propagation path of the AGWs into the atmosphere by solving a system of equations that govern their propagation. This methodology is similar to that of tracing a ray of light that propagates in a varying environment. In the present work, an AGW in the northeast of Brazil was observed with spectral characteristics that indicate association with the 21 August 2017 total solar eclipse. In addition, the ray path matched the Moon's shadow in the stratosphere corroborating with the observational inferences. The AGW was observed by optical instruments during the nighttime, more than 3 h after the end of the eclipse and over 2, 000 km away from the Moon's shadow. Key Points: A multi‐instrumented observational campaign was carried out in Brazil to study the effects of the 21 August 2017 solar eclipse Atmospheric gravity waves were observed in the airglow over the Northeastern Brazil Analyses including reverse ray tracing suggested the eclipse as the likely source for one observed medium‐scale gravity wave